The Authority of Police Investigative in Implementing Diversion on Children in Conflict with The Law as Reviewed from The Principles Best Interests of The Child (Study at the PPA Unit of the Grobogan Police) - Mustika Ayu Ariftiyani; M. Junaidi (Universitas Muhammadiyah Surakarta, 2026)
Introduction: Children, as individuals in their developmental phase, require special protection when dealing with the law to avoid the negative impacts of the formal justice system. This research is motivated by the important role of investigators from the Grobogan Police Women and Children Unit (PPA) in implementing diversion to guarantee children's rights. This research uses an empirical juridical approach to analyze the factual application of legal norms in the field.Method: Data was collected through in-depth interviews with investigators from the PPA Unit of the Grobogan Police and literature studies of related regulations.Novelty: The difference between this article and previous research lies in the specific analytical focus on the effectiveness of investigators' authority in the Grobogan Police jurisdiction in implementing the principle of the best interests of children through the provision of deliberation facilities and the involvement of community leaders as mediators.Results: The implementation of diversion at the Grobogan Police Women and Children Unit (PPA) is guided by the Child Protection and Child Protection Law (UU SPPA). Investigators act as neutral facilitators, providing deliberation facilities, while mediation is conducted with community leaders to maintain objectivity. The principle of the best interests of the child has been implemented through a communicative-persuasive approach, identity protection, and the fulfillment of children's rights during the investigation process to minimize psychological stress.Conclusion: The implementation of diversion at the Grobogan Police Women and Children Unit integrates formal regulations with social moral authority through collaborative facilitation involving community leaders. This legal protection prioritizes the principle of the child's best interests, taking into account their mental health and environment. social to prevent trauma and ensure the future well-being of children.